Haemodynamic Wall Shear Stress, Endothelial Permeability and Atherosclerosis—A Triad of Controversy - Weinberg, Peter D. (Frontiers in Bioengineering and Biotechnology, 2022)
A striking feature of atherosclerosis is its patchy distribution with the vascular system; certain arteries and certain locations within each artery are preferentially affected. Identifying the underlying local risk factors may lead to new therapeutic strategies. The large variation in lesion prevalence in areas of curvature and branching has motivated a search for haemodynamic triggers, particular those related to wall shear stress (WSS). The fact that lesions are rich in blood-derived lipids has motivated studies of local endothelial permeability. However, the location of lesions, the underlying haemodynamic triggers, the role of permeability, the routes by which lipids cross the endothelium, and how WSS affects permeability have all been areas of controversy. This review presents evidence for and against the current consensus that lesions are triggered by low and/or oscillatory WSS and that this type of shear profile leads to elevated wall entry of low density lipoprotein (LDL) via widened intercellular junctions, and it evaluates more recent evidence that lesion location changes with age, that multidirectional shear stress plays a key role, that LDL dominantly crosses the endothelium by transcytosis, and that the link between flow and permeability results from hitherto unrecognised shear-sensitive mediators.